Identification and Preliminary Evaluation of a Novel Recombinant Protein for Serodiagnosis of Strongyloidiasis - Arifin, Norsyahida (Am J Trop Med Hyg, 2018)
Strongyloides stercoralis is a human parasite that can cause a long-term infection. In immunosuppressed patients, strongyloidiasis may be fatal when there is overwhelming autoinfection resulting in the migration of large numbers of larvae through many organs. Definitive diagnosis is still a challenge, and a combination of symptoms, microscopic identification, and serology test results are often used to arrive at a clinical decision. However, intermittent larval excretion, low parasite burden, and occult infections are challenges with parasitological diagnosis of infection with S. stercoralis. Meanwhile, serologic tests using immunoglobulin G and parasite antigen extract have problems of cross-reactivity with other helminthic infections. Recombinant antigen-based serodiagnosis is a good alternative to overcome the laboratory diagnostic issues. Herein, we report on the isolation of cDNA clone encoding an antigen of potential diagnostic value identified from immunoscreening of a S. stercoralis cDNA library. The translated protein had highest similarity to Strongyloides ratti immunoglobulin-binding protein 1. The recombinant antigen produced, rSs1a, was assessed using western blot and enzyme-linked immunosorbent assay. The latter showed 96% diagnostic sensitivity and 93% specificity; thus, rSs1a has good potential for use in serodiagnosis of human strongyloidiasis.